SYSTEMATIC DESIGN OF A CONTROLLER BASED ON ARTIFICIAL INTELLIGENCE TECHNIQUES WITH APPLICATIONS TO WIND POWER - M. FAYEK, HAYTHAM (2014)
The expeditious growth ofwind power penetration has highlighted the need to study the impact of wind turbine generators on power systems. Researcher are currently exploring methods to improve the contribution of wind turbine generators to the dynamic stability of power systems. One such method is equipping Wind Turbine Doubly-Fed Induction Generators (WTDFIG) with Wind turbine generator Power System Stabilizers (WPSS). Presently, WPSSs are based on the conventional lead-lag compensator or proportional gain concepts, which suffer drawbacks in terms of handling power system nonlinearities, robustness anddesign practicality.